THE CLASSIFICATION OF CORPORATE STOCK EQUITIES. - Lowe, Howard D. (The Accounting Review, 1961)
Abstract With the development of the modern corporation, accounting reports have become more difficult to prepare and to interpret. Many of the problems are centered in that portion of the balance sheet identified as the net worth, proprietorship, or capital section. There are several explanations for the existence of these difficulties. One arises from the complexity of reporting the effect of such transactions as the issuance of shares, the payment of stock dividends, and the reacquisition and reassurance of shares, when ownership is diffused among different classes of stock each having special features. Another arises from the numerous and varied legal restrictions that directly or indirectly influence the reporting of corporate equities. The recent article by Professor Buttimer concerned with the statutory influence on accounting for treasure stock is an illustration of this problem.' It may be that accounting theory has not developed to the point necessary to define precisely the functions and objectives to he served by each item of information in the stockholders' equity section of the balance sheet. This is another explanation which may account for the wide variety of terminology used and the varied and often vague objectives attempted to be served.